Effectiveness of glass as a substitution for cement and fine aggregate in concrete mix - Adnan, Suraya Hani; Osman, Mohamad Hairi (Penerbit UTHM, 2017)
Concrete is a solid material which widely been used nowadays in construction industry. This solid material is produced when cement, coarse aggregate, fine aggregate, water and admixture are mixed thoroughly. Concrete is becoming a favourite choice because its basic ingredients are easily found, require little maintenance service, easy to handle, most economical material, good in compression, durable and good fire resistance. Concrete is produced when cement, coarse aggregate, fine aggregate, water and admixtures are mixed thoroughly. Concrete is defined as a good quality concrete when it enables to achieve good strength and durability (Neville, 2011). Good strength is achieved when concrete can sustain the maximum load. Meanwhile, good durability is achieved when concrete can resist attack from aggressive ion which delivered externally and internally. Good quality concrete can be produced by using several methods. One example is utilization of pozzolanic material. According to ASTM 618-94a, pozzolans is siliceous or siliceous and aluminous material which in itself possesses little or no cementitious value but will, in finely divided form and in the presence of moisture, chemically react with calcium hydroxide at ordinary temperature to form compounds possessing cementitious properties. Recently, pozzolanic material like fly ash, silica fume and ground granulated blastfurnace slag has been widely used in construction industry. Moreover, pozzolanic material has some benefits such as it can encourage the application of natural waste product and for environmental conservation (Sampaio, 2000). This is due that generally pozzolanic material is produced from by-product waste. Normally these pozzolanic materials functioning as cement replacement material which substitute a part of cement content.